Análise empírica sobre os determinantes da decisão de produção de açúcar e etanol na agroindústria canavieira paulista - De Lucca, Mariana Regina Zechin (2020)
Being able to produce ethanol and sugar from the same feedstock, sugarcane, is a competitive advantage of Brazil’s sugarcane industry. This operational flexibility is unique in the world and allows Brazilian mills to switch between both product outputs in response to changes in market conditions, even in the short term. Under this approach and considering the absence of studies on the subject, the present research investigates the factors that influence the decision-making process concerning the allocation of sugarcane for sugar and ethanol production. Two models were designed and estimated based on a panel data of 119 mills. All these mills are flexible plants, producing either sugar or ethanol from 2010/2011 to 2018/2019 crop year and located in São Paulo state, the main sugarcane cultivation region in the country. While one model took as dependent variable the produced amount of hydrous ethanol (in liters) and sugar (in kg) per ton of crushed sugarcane, the other one used the production mix (the share of sugarcane diverted to produce sugar and ethanol) as an endogenous element. The results indicated that prices were the main factors affecting the mill’s decision. However, technical variables also influenced the business strategy, namely: the raw material quality; number of days that the facility was operating during a single harvest season; the production capacity; and the effective use of available milling capacity. In addition, the supply elasticity was calculated using the midpoint method. The supply was price inelastic, reaching 0.378 for sugar and 0.384 for ethanol.